Modifiable lifestyle factors influencing the severity of atopic dermatitis – implications for prevention and health education: a literature review - Bort, Julia; Syncerz, Natalia; Zadrożna, Katarzyna; Cupryś, Kamila; Wójcik, Bartłomiej; Czajka, Katarzyna; Borodacz, Julia; Czampiel, Martyna; Nawracaj, Michał; Dryżałowski, Piotr (Journal of Education, Health and Sport, 2026)
Atopic dermatitis (AD) is a chronic, relapsing, immune-mediated inflammatory skin disorder characterized by intense pruritus, erythema and dry, scaly lesions. Its clinical presentation varies by age. AD is frequently associated with other IgE-mediated conditions, such as allergic rhinitis, asthma, and food allergies. Genetic predisposition, immune dysregulation, and skin barrier dysfunction play central roles in pathogenesis. In addition, lifestyle and environmental factors- including diet, stress, sleep disturbances, physical activity, and environmental exposures- significantly influence disease severity and progression. Promoting individualized, evidence-based lifestyle interventions such as balanced diet, stress management, moderate physical activity, and environmental control- should be considered a shared responsibility among healthcare providers, patients, and caregivers in the management and prevention of atopic dermatitis.